Risk expectation from trade protectionism and firm innovation strategies: Theory and evidence from China - Zeyang Li; Feifei Fang (Journal of Innovation & Knowledge, 2024)
In this study, we construct a new measurement of a firm's trade risk expectation. We investigate how exporters’ innovation strategies respond to trade protection and their risk expectation by studying the global anti-dumping investigations against China. Specifically, using information on targeted products, we identify the trade risk level of each firm. We then develop a theoretical model to analyze how a multi-product firm adjusts its innovation strategies by its trade risk expectation when affected by anti-dumping measures, and the spillover effects of trade risk expectation on the firm's innovation strategies. This model predicts that first, affected firms will increase their R&D investment and innovation output in response to the increase of trade risk. Second, firms are more likely to choose high-quality innovation when their trade risk expectations increase. Third, for unaffected firms, an increase in trade risk expectation will lead to a growth in their innovation outputs. These predictions are aligned with the Chinese data, which are matched with an anti-dumping dataset from the Global Anti-dumping Database and several firm-level datasets. After changing the definition of trade risk expectation, excluding the cases also affected by countervailing measures and those with a zero anti-dumping tax rate, our results remain constant. This gives us further confidence that exporters with higher trade risks are more responsive to trade protection.